Large-area organic photovoltaic modules with 14.5% certified world record efficiency - Basu, Robin; Gumpert, Fabian; Lohbreier, Jan; Morin, Pierre Olivier; Vohra, Varun; Liu, Yang; Zhou, Yinhua; Brabec, Christoph; Egelhaaf, Hans-Joachim; Distler, Andreas (Joule, 2024)
Organic photovoltaics (OPVs) have experienced a significant increase in power conversion efficiency (PCE) recently, now approaching 20% on small-cell level. Since the efficiencies on the module level are still substantially lower, focused upscaling research is necessary to reduce the gap between cells and modules. In this work, we present the upscaling of PM6:Y6-C12:PC61BM-based devices, processed in ambient air from non-halogenated solvents, from small-area cells to large-area modules with barely any performance loss. Supported by computational fluid dynamics simulations, an accelerated blade coating process that enables homogeneous coatings with <5% thickness deviation over 200 cm² is developed. Additional finite element method simulations are used to optimize the module layout and minimize the inevitable losses caused by electrode resistances and inactive interconnect areas to 1.9% and 3.5%, respectively. Finally, a 204-cm² OPV module with a certified PCE of 14.5% (15.0% on active area) is fabricated, which constitutes the new world record.
CRIS-Team Scopus Importer:2024-04-05
Keywords: certified world record efficiency; FEM simulations; laser patterning; OPVs; organic photovoltaics; process optimization; solar modules; solution-processed in ambient air